Economic Status of the Theppam Fishery In Negambo - Weerasinghe, L.S.A. (university of Sri Jayewardenepura, Gangodawila, Nugegoda, 2009)
Economic analysis of' 'l'heppam fishery was made from April 2008 to December 2008. 'l'heppama" is a traditional fishing craft and usually fishing is carried out with small meshed gilinets. Fishing operation was limited to the region within 0.8km - 1 .5km from the shore and depth is about 7m -10 m. More than 45% of the fishermen fished at 9m depth and more than 50% catch were recorded from the 9m depth. Usually. Theppam fishermen depart from the shore about 3.30am to 4.00am and return to shore about 7.30am to 8.00am actual elfictive time of fishing is range 1 hour to 2hours. In early stages. Theppam were made out of timber, but now Theppams are made out with Fiber Reinforced Plastics. Alter 1950s some Theppams were powered with out board engines. But in the study area only non motorized plastic Theppams were found and they were operated using an oar. Sizes of the Theppam's are range from 11 .l5t to I 2.Sft in length. Crew size of the Theppam is usually one. Gillnets were the main gear use in Theppam fishery. Length of the one net piece was 1500 meshes and width of the one net piece was 330 meshes. Usually 4-6 net pieces were used. 12mm, 19mm, 23mm, 28mm. 45mm and 50mm stretched mesh nets were operated during the study period. July to September was the peak period to Thepparn fishery. Sardine/Ia sp were the main fish sp contributes tothe catch. They contribute about 50% of the total catches. Daily catch ranged from 0 - 15kg. The lowest estimated annual catch of a Theppam was 1357kg and the highest was 2001 kg. Estimated annual total catch from the study area was 29443 kg. Daily income of a Theppam ranged from 0 to 2350 rupees. Estimated annual income was 206744 to 302833 rupees. Daily cost of operation Theppam ranged from 0 to 1000 rupees while estimated annual operational cost was 288 to 5750 rupees. Investing to a "Theppama" and Gilinets are the capital costs of a Theppam fishery. Price of a Theppama" ranged 24,000 - 40,000 rupees and price of a twine multifilament gillnet is 7000 rupees. Theppams earn a profit which is 10 times its cost. It is a highly economic craft.